Antimicrobial Resistance Distribution Differs Among Methicillin Resistant Staphylococcus aureus Sequence Type (ST) 5 Isolates From Health Care and Agricultural Sources - Hau, Samantha J.; Haan, Jisun S.; Davies, Peter R.; Frana, Timothy; Nicholson, Tracy L. (Frontiers in Microbiology, 2018)
Antimicrobial resistance is an expanding public health concern and methicillin resistant Staphylococcus aureus (MRSA) is a notable example. Since the discovery of livestock associated MRSA (LA-MRSA), public health concerns have arisen surrounding the potential of LA-MRSA isolates to serve as a reservoir for antimicrobial resistance determinants. In this study, we compare swine associated LA-MRSA ST5 and human clinical MRSA ST5 isolates for phenotypic antimicrobial susceptibilities determined via broth microdilution and genotypic determinants of antimicrobial resistance using whole genome sequencing and comparative genomic analysis to identify antimicrobial resistance elements. Swine associated LA-MRSA ST5 isolates exhibited phenotypic resistance to fewer antibiotics than clinical MRSA ST5 isolates from humans with no swine contact. Distinct genomic antimicrobial resistance elements were harbored by each subgroup, with little overlap in shared antimicrobial resistance genes between swine associated LA-MRSA ST5 and clinical MRSA ST5 isolates. Our results demonstrate that phenotypic antimicrobial susceptibilities and genotypic determinants of antimicrobial resistance among swine associated LA-MRSA ST5 and clinical MRSA ST5 isolates are separate and distinct suggesting that ST5 MRSA isolates from agricultural sources are not acting as a source of antimicrobial resistance elements for the clinical human ST5 MRSA isolates tested here.